2013
DOI: 10.1590/s0102-33062013000400017
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation of inoculation with Glomus proliferum and application of humic acid in the in vitro growth of Lunularia cruciata

Abstract: In this study, we evaluated the growth of the liverwort Lunularia cruciata, inoculated or not with the arbuscular mycorrhizal fungi (AMF) Glomus proliferum (15 spores per Petri dish), in Strullu-Romand Variant (SRV) medium modified and enriched with humic acid (HA) at different concentrations (0, 20, 40 and 80 mg C L −1 ), as well as the sporulation of the AMF. We assessed the absolute growth rate (AGR) and relative growth rate (RGR) at inoculation, as well as at 7, 14, 21, 28, 43, 52 and 60 days after inocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The HS‐And treatment stimulated spore density less strongly than the other HS treatments. The HS stimulation of sporulation was reported by Nobre et al (2013), with a significant increase in the sporulation of Glomus proliferum combined with Lunaria cruciata due to the effect of HA under in vitro conditions. The stimulation of mycorrhizal colonization and spore density by HS application has been explained in other studies by the ability of SOM to stimulate AMF development, especially mycelial growth, root colonization, and the intra‐ and extraradicular development of Glomus claroideum hyphae (Gryndler et al, 2005, 2009).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The HS‐And treatment stimulated spore density less strongly than the other HS treatments. The HS stimulation of sporulation was reported by Nobre et al (2013), with a significant increase in the sporulation of Glomus proliferum combined with Lunaria cruciata due to the effect of HA under in vitro conditions. The stimulation of mycorrhizal colonization and spore density by HS application has been explained in other studies by the ability of SOM to stimulate AMF development, especially mycelial growth, root colonization, and the intra‐ and extraradicular development of Glomus claroideum hyphae (Gryndler et al, 2005, 2009).…”
Section: Resultsmentioning
confidence: 70%
“…The addition of differently sourced organic components, such as cellulose, and different types of substrates or composted biomass has been shown to stimulate the production and quantity of intra‐ and extraradical hyphae (Gryndler et al, 2002); this effect has also been confirmed under hydroponic conditions (Gryndler et al, 2005). Reports exist regarding the application under axenic conditions of humic acids (HA) extracted from vermicompost (Vc) to stimulate the production of Glomus proliferum spores, the growth of Lunaria cruciata (Nobre et al, 2013), and the mycorrhizal colonization of Glomus clarum on clover ( Trifolium repens L.) and basil ( Ocimum basilicum L.) roots (Lima, 2008).…”
mentioning
confidence: 99%
“…These changes may have affected plant interactions with AMF. For instance, increased release of phosphorus may reduce AMF colonization whereas higher levels of humic acids can often be well combined with successful establishment and growth promoting effects of AMF ( Nobre et al., 2013 ; Cozzolino et al., 2016 ). Sterilized soils were stored at room temperature until use.…”
Section: Methodsmentioning
confidence: 99%